The invisible life of addie larue ebook - Schwab, V. E. (2020)
NEW YORK TIMES BESTSELLER USA TODAY BESTSELLER NATIONAL INDIE BESTSELLER THE WASHINGTON POST BESTSELLER Recommended by Entertainment Weekly , Real Simple , NPR , Slate , and Oprah Magazine #1 Library Reads Pick — October 2020 #1 Indie Next Pick — October 2020 BOOK OF THE YEAR (2020) FINALIST — Book of The Month Club A "Best Of" Book From: Oprah Mag * CNN * Amazon * Amazon Editors * NPR * Goodreads * Bustle * PopSugar * BuzzFeed * Barnes & Noble * Kirkus Reviews * Lambda Literary * Nerdette * The Nerd Daily * Polygon * Library Reads * io9 * Smart Bitches Trashy Books * LiteraryHub * Medium * BookBub * The Mary Sue * Chicago Tribune * NY Daily News * SyFy Wire * Powells.com * Bookish * Book Riot * Library Reads Voter Favorite * In the vein of The Time Traveler's Wife and Life After Life , The Invisible Life of Addie LaRue is New York Times bestselling author V. E. Schwab's genre-defying tour de force. A Life No One Will Remember. A Story You Will Never Forget. France, 1714: in a moment of desperation, a young woman makes a Faustian bargain to live forever—and is cursed to be forgotten by everyone she meets. Thus begins the extraordinary life of Addie LaRue, and a dazzling adventure that will play out across centuries and continents, across history and art, as a young woman learns how far she will go to leave her mark on the world. But everything changes when, after nearly 300 years, Addie stumbles across a young man in a hidden bookstore and he remembers her name. Also by V. E. Schwab Shades of Magic A Darker Shade of Magic A Gathering of Shadows A Conjuring of Light Villains Vicious Vengeful At the Publisher's request, this title is being sold without Digital Rights Management Software (DRM) applied.